2014
DOI: 10.1017/s1431927614000968
|View full text |Cite
|
Sign up to set email alerts
|

Toward Site-Specific Dopant Contrast in Scanning Electron Microscopy

Abstract: Since semiconductor devices are being scaled down to dimensions of several nanometers there is a growing need for techniques capable of quantitative analysis of dopant concentrations at the nanometer scale in all three dimensions. Imaging dopant contrast by scanning electron microscopy (SEM) is a very promising method, but many unresolved issues hinder its routine application for device analysis, especially in cases of buried layers where site-specific sample preparation is challenging. Here, we report on opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…For the freshly cleaved specimen, p was brighter than n under standard imaging conditions (Fig. 1b), as expected (Oatley & Everhart, 1957; Perovic et al, 1995, 1998; Venables et al, 1998; Elliott et al, 2000; Sealy et al, 2000; Elliott, 2001; Elliott et al, 2002; Lin & Lee, 2003; El-Gomati et al, 2004; Buzzo et al, 2006, 2007; Chee et al, 2008 a , 2008 b ; Chee et al, 2010, 2011; Liu & Lee, 2011 a , 2011 b ; Chung et al, 2011; Farrell et al, 2013; Xu et al, 2013; Druckmüllerová et al, 2014; Chee, 2016 a ; Alugubelli et al, 2019; Chee, 2019, 2020). Moreover, surface treatment using fresh (degraded) NH 4 F (aq.)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the freshly cleaved specimen, p was brighter than n under standard imaging conditions (Fig. 1b), as expected (Oatley & Everhart, 1957; Perovic et al, 1995, 1998; Venables et al, 1998; Elliott et al, 2000; Sealy et al, 2000; Elliott, 2001; Elliott et al, 2002; Lin & Lee, 2003; El-Gomati et al, 2004; Buzzo et al, 2006, 2007; Chee et al, 2008 a , 2008 b ; Chee et al, 2010, 2011; Liu & Lee, 2011 a , 2011 b ; Chung et al, 2011; Farrell et al, 2013; Xu et al, 2013; Druckmüllerová et al, 2014; Chee, 2016 a ; Alugubelli et al, 2019; Chee, 2019, 2020). Moreover, surface treatment using fresh (degraded) NH 4 F (aq.)…”
Section: Resultsmentioning
confidence: 99%
“…6a). Hence, other than the radically curtailed oxidation-and cleavage-related artifacts (Druckmüllerová et al, 2014), that the patch fields are abolished may explain the diminished scatter in the doping contrast data (Fig. 3b).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[23][24][25] However, the doping contrast formation is also dependent on the local external electric field, 26,27 surface band-bending field, 28,29 metal-semiconductor contacts, [30][31][32][33] refraction effects at the semiconductor-vacuum interface 34,35 and the collection solid angle of the SE detector. 24,36,37 Gallium nitride (GaN), one of the third-generation wide bandgap semiconductors, has received much attention owing to its high breakdown electric fields, high thermal conductivity, good chemical stability and strong irradiation resistance (related to its high internal and external quantum efficiencies). 38,39 Therefore, GaN has broad application prospects in the fields of optoelectronics, highpower devices and high-frequency microwave devices.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical results have shown that the doping contrast is mainly a function of bulk built‐in voltages of the p‐n junction 23–25 . However, the doping contrast formation is also dependent on the local external electric field, 26,27 surface band‐bending field, 28,29 metal–semiconductor contacts, 30–33 refraction effects at the semiconductor–vacuum interface 34,35 and the collection solid angle of the SE detector 24,36,37 …”
Section: Introductionmentioning
confidence: 99%